Review of Recent Detection Methods for HTTP DDoS Attack - Jaafar, Ghafar A.; Abdullah, Shahidan M.; Ismail, Saifuladli (Journal of Computer Networks and Communications, 2019)
With increment in dependency on web technology, a commensurate increase has been noted in destructive attempts to disrupt the essential web technologies, hence leading to service failures. Web servers that run on Hypertext Transfer Protocol (HTTP) are exposed to denial-of-service (DoS) attacks. A sophisticated version of this attack known as distributed denial of service (DDOS) is among the most dangerous Internet attacks, with the ability to overwhelm a web server, thereby slowing it down and potentially taking it down completely. This paper reviewed 12 recent detection of DDoS attack at the application layer published between January 2014 and December 2018. A summary of each detection method is summarised in table view, along with in-depth critical analysis, for future studies to conduct research pertaining to detection of HTTP DDoS attack.